Pengelolaan Harta Masyarakat Kelas Menengah Daerah Nganjuk dengan Pendekatan Religiosity Financial Planning - Muhammad Fatchullah El Islami; Mustofa (At-Taradhi Jurnal Studi Ekonomi, 2023)
Islamic wealth management is often equated with property management in general. Of course, both have significant differences, such as the existence of boundaries following Islamic teachings. This study aims to describe the expenditure and distribution of assets for religious purposes as stated in Religiosity Financial Planning. This research focuses on the middle-class community of Ngronggot Nganjuk. This study used a descriptive-quantitative approach. Data was collected through questionnaire dissemination. The number of respondents to this study was 60. The results showed that the ngronggot nganjuk community, in planning property for religious purposes, had done well, such as in planning zakat, infaq, sadaqah, qurban, and hajj. It is just that the planning of waqf, hibahs, and umrah is still not planned by all respondents. These results interpret that the behaviour of the middle-class community of Ngronggot village is influenced by several aspects: attitudes, subjective norms, and behavioural control.